1995
DOI: 10.2224/sbp.1995.23.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Basic Temperament Components of Loneliness, Shyness, and Conformity

Abstract: The PAD Temperament Model provides a general framework for personality description and consists of three nearly independent dimensions: Trait Pleasure-displeasure, Trait Arousability, and Trait Dominance-submissiveness. The present study analyzed the Shyness, Loneliness, and Conformity scales within the PAD Model. Shyness resembled trait anxiety and neuroticism and was composed of unpleasant, arousable, and submissive characteristics, with submissiveness the strongest and arousability the weakest components. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
84
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 12 publications
3
84
1
3
Order By: Relevance
“…Participants responded on a 5-point scale (1 = strongly disagree to 5 = strongly agree). This scale showed internal consistency and construct validity (e.g., negative correlation with dominance, positive correlation with internalization of social norms) in past studies (Mehrabian & Stefl, 1995;Vartanian & Hopkinson, 2010). This scale was reliable in the present study (α = .77).…”
Section: Study 2 Methodssupporting
confidence: 70%
“…Participants responded on a 5-point scale (1 = strongly disagree to 5 = strongly agree). This scale showed internal consistency and construct validity (e.g., negative correlation with dominance, positive correlation with internalization of social norms) in past studies (Mehrabian & Stefl, 1995;Vartanian & Hopkinson, 2010). This scale was reliable in the present study (α = .77).…”
Section: Study 2 Methodssupporting
confidence: 70%
“…Conformity was measured using the 10-item conformity scale (Mehrabian & Stefl, 1995; e.g., "I often rely on, and act upon, the advice of others"; 1 = not at all true of me, 7 = extremely true of me; M = 3.42, SD = 0.89; a = .80). In both studies, participants gave their informed consent and reported demographics.…”
Section: Methodsmentioning
confidence: 99%
“…The conformity scale is an 11-item self-report measure assessing individuals' tendencies to conform to those around them (Mehrabian & Stefl, 1995). Participants were asked to respond to questions such as "I tend to rely on others when I have to make an important decision quickly" and "I don't give in to others easily" (reverse-coded) on a scale of 1 (not at all true of me) to 5 (extremely true of me).…”
Section: Methodsmentioning
confidence: 99%